Development and Testing of Baylor Scott & White Health's "Attitudes and Practices of Patient Safety Survey". Issue 4 (1st October 2016) - Barnes, Sunni A.; Compton, Jan; Saldaña, Margaret; Tecson, Kristen M.; Hastings, Chizuko; Kennerly, Donald A.
Abstract : Improving the quality of patient care requires a culture attuned to safety. We describe the development, implementation, and psychometric evaluation of the Attitudes and Practices of Patient Safety Survey (APPSS) within the Baylor Scott & White Health system. The APPSS was designed to enable safety culture data to be collected and aggregated at the unit level to identify high-priority needs. The survey, with 27 Likert-scale core questions divided into 4 concept domains and 2 open-ended questions, was administered electronically to employees with direct patient care responsibilities (n = 16, 950). The 2015 response rate was 50.4%. The Cronbach's α values for the four domains ranged from 0.78 to 0.90, indicating strong internal consistency. Confirmatory factor analysis results were mixed but were comparable to those of established safety culture surveys. Over the years, the adaptability of the APPSS has proven helpful to administrative and clinical leaders alike, and the survey responses have led to the creation of programs to improve the organization's patient safety culture. In conclusion, the APPSS provides a reliable measure of patient safety culture and may be useful to other health care organizations seeking to improve the quality and safety of the care they provide.